Comparison of conventional, amplitude-integrated and geodesic sensor net EEG used in premature neonates: a systematic review - Sousa, Tainã Maria Alves de; Gugelmin, Vinicius Siessere; Fernandes, Geraldo Magela; Aucélio, Carlos Nogueira; Costa, Karina Nascimento; Tristão, Rosana Maria (Arquivos de Neuro-Psiquiatria, 2019)
The use of methods to evaluate cortical activity in neonates has great importance in modern medicine, as it allows the observation and evaluation of several clinical aspects, which guarantees that the health team has knowledge about possible intervention measures that may be necessary in the treatment of newborns.Objective: This systematic review aimed to compare the main technologies available for the evaluation of brain functions in neonates, among them: the conventional electroencephalogram (EEG), the amplitude-integrated electroencephalogram (aEEG) and the geodesic sensor net EEG.Methods: A search was conducted forarticles from national and international periodicals included in the Web of Science, LILACS, SciELO and Medline electronic databases.Results: The search found 39 among 155 articles of interest and the analyses indicated that, in the clinical environment, the use of both conventional EEG and aEEG is highly recommended, as the combination of their functions allows, for example, a greater number of subclinical seizures to be detected. Conversely, the use of a geodesic sensor net EEG could be of great value, as it allows a large amount of data to be analyzed.Conclusion: This analysis may be useful in studies and research related to diseases and symptoms, such as seizures, a current challenge for neonatal neuromonitoring, as well as aspects of neurological development and functional studies. However, despite many advances in technology, electroencephalography in preterm neonates remains a challenge worldwide and still requires more robust research and efforts towards the best clinical assistance in this extremely early stage of life.
Keywords: Electroencephalograhy; intensive care units; neonatal; seizures